Sperm count and chromatin structure in men exposed to inorganic lead: lowest adverse effect levels. Issue 4 (1st April 2002) - Bonde, J P; Joffe, M; Apostoli, P; Dale, A; Kiss, P; Spano, M; Caruso, F; Giwercman, A; Bisanti, L; Porru, S; Vanhoorne, M; Comhaire, F; et al.
Abstract : Objectives: To obtain knowledge on male reproductive toxicity of inorganic lead at current European exposure levels and to establish lowest adverse effect levels, if any. Methods: A cross sectional survey of the semen of 503 men employed by 10 companies was conducted in the United Kingdom, Italy, and Belgium. The mean blood lead concentration was 31.0 μg/dl (range 4.6–64.5) in 362 workers exposed to lead and 4.4 μg/dl (range below the detection limit of 19.8) in 141 reference workers. Semen volume and sperm concentration were determined in a fresh semen sample according to an agreed protocol subject to quality assurance. The sperm chromatin structure assay (SCSA) was performed at a centralised laboratory. Extraneous determinants including centre, period of sexual abstinence, and age were taken into account in the statistical analysis. If appropriate, possible thresholds were examined by iterative threshold slope linear regression. Results: The median sperm concentration was reduced by 49% in men with blood lead concentration above 50 μg/dl. There was no indication of a linear trend of lower sperm concentration with increasing blood lead values, but threshold slope least square regression identified a blood lead concentration of 44 μg/dl (β=−0.037, F =4.35, p=0.038) as a likely threshold. Abnormal sperm chromatin structure was not related to blood lead concentration, but some indications of deterioration of sperm chromatin was found in men with the highest concentrations of lead within spermatozoa. Biological monitoring data did not indicate long term effects of lead on semen quantity or sperm chromatin. Conclusion: Adverse effects of lead on sperm concentration and susceptibility to acid induced denaturation of sperm chromatin are unlikely at blood lead concentrations below 45 μg/dl. Effects of low level exposure to lead on other measures of testicular function cannot be ruled out.